Effects of common carp Cyprinus carpio (L.) and feed addition in rohu Labeo rohita (Hamilton) ponds on nutrient partitioning among fish, plankton and benthos - Rahman, Mohammad Mustafizur; Verdegem, Marc; Nagelkerke, Leo; Wahab, Md Abdul; Milstein, Ana; Verreth, Johan (Wiley-Blackwell, 2008)
The effects of introducing common carp (CC) and of adding artificial feed to fertilized rohu ponds on water quality and nutrient accumulation efficiency were studied. All ponds were stocked with 15000 rohu ha-1. Treatments included ponds with rohu alone, rohu plus 5000 common carp ha-1 and rohu plus 10000CC ha-1. Acomparisonwas alsomade between supplementally fed and non-fed ponds. The overall highest nitrogen (N) and phosphorus (P) concentrations were observed in ponds with 5000 CC ha-1, followed by ponds with 10000 and 0 CC ha-1. The largest fractions of Nand Pinputs accumulating in fish, phytoplankton and zooplankton were observed in ponds with 5000 CC ha-1, followed by ponds with 10000CC ha-1 and subsequently ponds without CC. Relatively more nutrients accumulated in benthic organisms in ponds without than in ponds with CC. A smaller fraction of the nutrient input was retained in fish, plankton and benthic organisms in pondswithout CC compared with ponds with CC. Compared with 5000 CC ha-1, stocking10000 CC ha-1 canbe considered as overstocking, because this leads to lower ¢sh production and relatively less nutrients retained in plankton and benthic organisms.